1993
DOI: 10.1007/bf01474679
|View full text |Cite
|
Sign up to set email alerts
|

?2 and ?-adrenergic stimulation of corticosterone secretion in rats

Abstract: Bilateral injection of 6-hydroxydopamine into the medial forebrain bundle (MFB) significantly decreased monoamine concentrations in the hypothalamus. The noradrenaline and serotonin content of the paraventricular nucleus (PVN) was also significantly reduced. These drastic decreases in neurotransmitter concentration did not alter basal secretion of corticosterone. Isoproterenol, a beta-adrenoceptor agonist (1 mg/kg, i.p.), significantly stimulated corticosterone release in saline and MFB lesioned rats. This sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The reasons for the inability of all three adrenergic agonists to increase CS by themselves are unclear. This could be due to the fact that the doses of CLON, PHE and ISO that were used in the present study were lower compared to others that examined the effects of these compounds on CS levels (Bugajski et al, 1995;Bugajski et al, 1991;Daniels et al, 1993;Gadek-Michalska et al, 1990;Saphier and Feldman, 1989). However, results from the present study indicate that these doses were effective in dissecting the roles of adrenergic receptors in leptin-induced decrease in CS secretion.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The reasons for the inability of all three adrenergic agonists to increase CS by themselves are unclear. This could be due to the fact that the doses of CLON, PHE and ISO that were used in the present study were lower compared to others that examined the effects of these compounds on CS levels (Bugajski et al, 1995;Bugajski et al, 1991;Daniels et al, 1993;Gadek-Michalska et al, 1990;Saphier and Feldman, 1989). However, results from the present study indicate that these doses were effective in dissecting the roles of adrenergic receptors in leptin-induced decrease in CS secretion.…”
Section: Discussionmentioning
confidence: 72%
“…A number of studies have investigated the role of adrenergic receptors in the regulation of CS. Systemic administration of CLON was able to reverse CS suppression after NE depletion (Daniels et al, 1993) and CLON by itself can also increase CS secretion (Daniels et al, 1993). Similarly, PHE, a selective α 1 adrenergic agonist, stimulates CS secretion (Bugajski et al, 1995;Saphier and Feldman, 1989) which was blocked by an adrenergic antagonist prazosin (Gadek-Michalska et al, 1990;Saphier and Feldman, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the observed stimulatory changes in brain function are most likely due to afferent autonomic sensory nerve inputs [13] proposing that isoproterenol administration should provide a highly controllable experimental model to test interoceptive processes [13]. On the other hand, it should also be considered the possibility that the observed central effects could be mediated by the release of peripheral hormones induced by isoproterenol [28,29]. As far as corticosterone is concerned, this hypothesis does not provide a possible explanation to the effect observed in the present study, since isoproterenol at the dose of 5 mg kg −1 did not modify the plasma corticosterone levels.…”
Section: Discussionmentioning
confidence: 97%
“…Hohlbaum et al, claimed that the increase of corticosterone in anesthetized animals occurred due to the stress caused by the containment of the animals, and that corticosterone returned toward to basal levels after repeated applications, which may cause habituation to the procedure [ 38 ]. However, xylazine can modulate the secretion of glucoregulatory hormones in a dose-dependent manner [ 13 , 39 ]. Therefore, it is reasonable to suggest that the pharmacological action of these anesthetics is intimately related to corticosterone levels, and that the stress caused by the injection may not be the only factor responsible for the increase of corticosterone.…”
Section: Main Textmentioning
confidence: 99%